Answer:
Explicit tn = 52 + (n - 1)*(-12)
Recursive = tn = t(n - 1) - 12
Step-by-step explanation:
The difference between term n and term n - 1 is can be found by taking the difference between and 2 consecutive terms.
t3 = 28
t2 = 40
d = t3 - t2
d = 28 - 40
d = - 12
Explicit
tn = a1 + (n - 1)*d
a1 = 52
tn = 52 + (n - 1)*(-12)
<em><u>Example</u></em>
Find t5
t5 = 52 + (5 - 1)*(-12)
t5 = 52 + 4 * - 12
t5 = 52 - 48
t5 = 4
Recursive
tn = t(n - 1) - 12
t5 = t4 - 12
t5 = 16 - 12
t5 = 4 just as it did before.
d
the answer orange is n=3
No
If OR = 20,
PR = 5
<u><em>OP would be</em></u>:
=> 20+5
=> 25